(untitled) (Applied Biological Research, 2023)
The purpose of this study was to compare the kinetic parameters of counter movement jump between sports players in flatfoot and normal foot groups. In this cross-sectional study, random sampling method was used to draw a group of 20 players with normal foot and a group of 20 players with flatfoot. Navicular drop test was used to classify two groups (flat foot and normal foot). Quattro Jump Kistler force platform (model 9290DD) was used to record kinetic parameters of Countermovement jump. The findings of this study showed that the players with flatfoot exhibited higher peak vertical ground reaction forces (VGRFs) (p < 0.001) and lower push-off force impulse (p < 0.001) than players in normal foot group; however, no significant differences were observed in jump height and average force between the normal foot and flatfoot groups (p > 0.05). The results revealed that flatfoot has no effect on jump height but have significant impact on other kinetic parameters of jump performance. Players with flatfoot produced higher VGRFs during landing which may lead to greater forces imposed on foot region as compared to the players with normal foot which can induce various musculoskeletal injuries.